HUBUNGAN FAKTOR RISIKO PENCEMARAN SUMUR GALI DENGAN KUALITAS BAKTERIOLOGIS DI LINGKUNGAN PEMUKIMAN RW IV KELURAHAN JABUNGAN KOTA SEMARANG - Puji Rahayu; Tri Joko; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2019)
One of the facilities for supplying clean water used by the community in RW IV of Jabungan Village, Semarang City is a dug well. Of the 31 wells, there are 16 residents who use it for drinking water. In 2017, RW IV there were 20 cases of diarrhea with 9 children and 11 adults. In 2017, in RW IV, 3 samples of total coliform well water were examined with a total sample of> 300 CFU / 100 ml. The aim of this study was to analyze the relationship between risk factors for well water pollution and bacteriological quality of water in RW IV of Jabungan Village. This type of research is an observational analytic study with a cross sectional approach. The population of this study was all dug wells in RW IV of Jabungan Village. The research subjects were 31 wells with total sampling. The results of the study using the Chi-square test showed that there was a relationship and a risk factor between the waterlogging variables around the well (p = 0.004, CI-1.003-3.229), SPAL conditions (p = 0.002, CI = 1,000-3,999), well floor conditions (p = 0.004, CI = 1.003-3.299), the condition of standing water on the well floor (p = 0.043, CI = 1.005-1.850), the condition of the well floor crack (p = 0.032, CI = 1.005-1.950), bucket location & rope timba (p = 0.004, CI = 1,003-3,229), and the condition of the well wall (p = 0,007, CI = 1,005-2,765) on the total bacterial quality of coliform well water, but on the variable latrine distance (p = 0,001, CI = 0,992- 5,489), other pollutant distance (p = 0,008, CI = 0,819-7,052), well lip condition (p = 0,016, CI = 0,859-4,291) related but protective factors. The conclusion of this study is that there is a significant relationship between the quality of the digging well water bacteria with toilet distance, other pollutant distances, water around the well, SPAL conditions, well floor conditions, standing water conditions on the well floor, well floor cracking condition, bucket & rope location timba, the condition of the well lip and the condition of the well wall.